Genetic Divergence among Inbred Lines of Pumpkin (Cucurbita moschata Duch Ex Poir) (Bangladesh Journal of Plant Breeding and Genetics, 2016)
Genetic divergence among nineteen inbred lines of pumpkin (Cucurbita moschata Duch Ex Poir) was estimated through principal component analysis and Mohalanobiss D2 analysis. Inbred lines were grouped into five clusters. Cluster I, II, III, IV and V were composed of five, three, four, six and one inbred lines respectively. Maximum inter cluster distance was observed between the cluster III and V (72.69) followed by the cluster I and V (63.33). Minimum inter cluster distance was observed between cluster II and IV (10.64). The mean value of cluster III indicated the importance of days to first male and female flower open, node order to 1st female flower open and TSS.  Cluster IV showed the importance of days to first female flower open, fruit diameter, cavity diameter, flesh thickness and average fruit weight. Similarly, cluster V indicated the importance of yield per plant, fruits per plant and fruit length. Days to first male and female flower open, fruit length and cavity length had the highest contribution towards divergence among the inbred lines. Considering the magnitude of cluster distance, cluster means for different characters and contribution of characters towards divergence, the inbred lines from clusters I, III and IV could be selected as parent for hybridization program.